Unauthorized Dispositions of Trust Property: Tracing in Quebec Law - Smith, Lionel (McGill Law Journal / Revue de droit de McGill, 2013)
The trustee of a Quebec trust is an administrator of the property of others, with full administration. As such, he holds a wide range of powers over the trust property; typically, his powers will exceed his authority, in the sense that it will be possible for him to make unlawful dispositions of the trust property. In such a case, he will be liable of course, but sometimes, particularly if the trustee is insolvent or absent, it will be important to understand the effects of the unauthorized dispositions on the trust property. For example, it may be possible for beneficiaries or other interested parties to annul a disposition of trust property; in this way, the property may be restored to the trust patrimony. Somewhat more difficult is the case in which the trustee has improperly disposed of trust property in exchange for some other property, in an attempt to misappropriate trust assets and turn them to his own benefit. If it is not possible to annul the disposition, might it be possible to claim that the proceeds of this unauthorized disposition are themselves held in trust? This paper examines the extent to which the idea of real subrogation can be used to protect the trust patrimony. Although the Supreme Court of Canada has suggested that Quebec law does not have a general principle of real subrogation, the author argues that this principle has a role to play in protecting universalities of law and that it can appropriately be invoked in the context of unauthorized dispositions of trust property.